2022
DOI: 10.1037/xge0001172
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between autonomous and predetermined paradigms: The role of sampling in evaluative learning.

Abstract: Whereas most evaluative learning paradigms remove participants’ autonomy over the information they receive, other research traditions have demonstrated that information sampling has an important role in learning. We investigated the impact of information sampling on a central evaluative learning paradigm: evaluative conditioning. We compared a traditional evaluative conditioning paradigm with a paradigm in which participants have autonomy over the stimulus pairings they receive. Participants in the high-autono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 70 publications
(127 reference statements)
0
5
0
Order By: Relevance
“…Participants. As effect size estimations were not available for this first experiment, we based our sample size estimation on a previous, similar experiment conducted in our lab (Hütter et al, 2021), which estimated required sample size at N = 74. Moreover, the experiment was embedded in an experimental session containing other unrelated experiments, which allowed us to collect data of 83 participants.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants. As effect size estimations were not available for this first experiment, we based our sample size estimation on a previous, similar experiment conducted in our lab (Hütter et al, 2021), which estimated required sample size at N = 74. Moreover, the experiment was embedded in an experimental session containing other unrelated experiments, which allowed us to collect data of 83 participants.…”
Section: Methodsmentioning
confidence: 99%
“…As we expect that the goal will affect sampling strategies and, consequently, the sample obtained (H1) and that social targets will be evaluated according to the obtained samples (H2), we expect sample size to (partially) mediate the relationship between the sample (actuarial judgment) and the impression formed. In other words, participants will continue sampling those interaction partners they already have a positive impression of (e.g., Fiedler, 2000;Hütter, Niese, & Ihmels, 2021). Thus, sample size will be larger for trustworthy interaction partners.…”
Section: Overview Of Experiments and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because monitoring and control are intertwined in the quality checks performed during cognitive tasks, many MM findings entail blends of both metacognitive functions. For instance, Hütter et al’s (2022) recent research on evaluative conditioning revealed a combination of myopia for stimulus monitoring and feedback control. Unlike in traditional designs but in line with real life, participants could themselves sample conditioned-stimulus faces that were paired with positive or negative pictures as unconditioned stimuli, according to an experimental feedback plan.…”
Section: Blends Of Monitoring and Control Difficultiesmentioning
confidence: 99%
“…That is, the increased closeness toward the stronger reciprocator is due to the more frequent reciprocation of the participants' selection decisions by the stronger reciprocator. However, an alternative explanation, the selection‐based one, in terms of a sampling decision effect (Hütter et al, 2022) might be proposed. Specifically, according to Hütter and colleagues (2022), actively selecting a stimulus (i.e., an interaction partner) increases the liking of the stimulus and therefore, selecting one of the two targets more frequently might be enough to induce increased closeness within our paradigm.…”
Section: Mechanisms and Explanationsmentioning
confidence: 99%